Paradiplomasi Surabaya-Busan di Sektor Pariwisata Tahun 2010-2019 - Ahzani, W.K Faizin; Prakasa, Maulana Wahyu; Chidlir, Newfreedo (Global and Policy Journal of International Relations, 2020)
ABSTRACTDiplomacy is how to gain political or economic cooperation with other actors of international relations for any national interest purpose. In the modern era, diplomacy has their own form for specific matter and context of bilateral relations. Today's bilateral relations are cannot be defined to be just by state relationship with, but local government can become an actor by itself without the state. Paradiplomacy became a solution for inter-local cooperation after cold war era, and the evolution of paradiplomacy make the scope became wider in several sectors. It is just because the scope of this type of diplomacy is focussed on sub-state level and gives freedom to sub-states to determine their regional policies more freely. Paradiplomacy concept more specifically can be refers to sister-city, which means to become a powerful tool for capacity building, learning, economic, and social development in developing countries. Surabaya (Indonesian) and Busan (South Korea) are the example of paradiplomacy between developing state and developed state with local-regional focus. Tourism is one of the other sectors of cooperation between those states and have a spillover effect over culture exchange and also in society sector.Keywords: paradiplomacy, sister-city, sub-state, tourism, spillover effectDiplomasi merupakan cara bagaimana menjalin kerjasama politik dan ekonomi dengan aktor internasional lainnya untuk mencapai segala kepentingan nasional. Di era modern, diplomasi memiliki bentuk tersendiri untuk masalah yang lebih spesifik dan konteks hubungan bilateral. Di era sekarang diplomasi tidak dapat diartikan sebagai hubungan antar negara saja, melainkan pemerintahan lokal dapat menjadi aktor tersendiri tanpa negara. Paradiplomasi menjadi solusi bagi kerjasama antar pemerintah lokal setelah perang dingin, dan evolusi dari paradiplomasi membuat lingkup pembahasan menjadi lebih luas dalam beberapa sektor. Hal tersebut dikarenakan lingkup pembahasan dari diplomasi ini berfokus pada tingkat sub-negara dan memberikan kebebasan bagi sub-negara untuk menentukan kebijakan wilayah lebih bebas. Konsep paradiplomasi secara spesifik dapat merujuk ke sister-city yang berarti dapat menjadi alat pembangunan kapasitas, pembelajaran, ekonomi, dan pembangunan sosial di negara berkembang. Surabaya (Indonesia) dan Busan (Korea Selatan) merupakan contoh paradiplomasi antara negara berkembang dan negara maju dengan fokus wilayah-lokal. Pariwisata merupakan salah satu sektor kerjasama antara kedua negara tersebut dan memiliki efek spillover atas pertukaran budaya dan juga pada bidang lainnya.Kata Kunci: paradiplomasi, sister-city, sub-nasional, efek spillover